Competitive strategy to increase rural saving in micro segment of PT Bank Rakyat Indonesia Tbk branch office Medan Iskandar Muda - Ferdiantes, Ferdiantes; Nazaruddin, Nazaruddin; Sembiring, Meilita Tryana; Sriwardany, Sriwardany; Fadhilah, Dita Deviana (Institute of Computer Science (IOCS), 2024)
The growth of credit disbursements is expected to coincide with the growth of rural saving. However, credit growth is currently higher. This study aims to analyze the competitive strategy of PT Bank Rakyat Indonesia Tbk Branch Office Medan Iskandar Muda in improving rural saving. The location of this research was determined purposively, that the location chosen was a branch which was the largest bigbond in the Medan region. This research is qualitative research using descriptive methods to conduct data analysis. Analysis of competitive strategies in this study was carried out using the concept of Porter's Five Forces. The results of the analysis found that the competitive advantage lies in the network owned by PT Bank Rakyat Indonesia Tbk Branch Office Medan Iskandar Muda as well as the existence of individual customers and Micro, Small and Medium Enterprises. Our interviews with micro debtors found that most of the funds were used for business and consumption expenditures in wholesalers, traditional markets, supermarkets and large agents, while a small part was for savings and repayments. So that with its competitive advantage, the mastery of acceptance in wholesalers, markets, supermarkets and large agents will increase rural saving.